CATEGORY OF “CONTINGENCY” AS A FACTOR IN THE LEGITIMIZATION OF TOLERANCE AND PLURALISM - Karipbaev , B.I. (Academic Journal of Physical and Chemical Sciences, 2018)
The article highlights the issues of multiculturalism of the modern globalizing world in terms of the complexity of establishing a tolerant relationship between irreducible pluralistic positions of different cultures and suggests their neo-pragmatic interpretation through the centralization of the category of “contingency”. The relevance of the article is directly conditioned by the current world situation, marked by growing tendencies of cooperation, communication and parity polylogues, but in practice, they reveal some difficulties (and sometimes insuperable) of building a proper level of tolerant relationships. The method used in this study, in the classical philosophical tradition was called “transcendental”. It is aimed at identifying the conditions for the possibility of realizing a particular phenomenon. In our case, it is the crisis of traditional cultural strategies of the West in relation to the rest of the world. As a result of applying the transcendental method to the situation of an urgent crisis, we formulate the basic meanings of the self-consciousness of Western culture, conceptualization of which clarifies the causal connection between the past and the present and, thus, explains the nature of the reasons that led to the actual crisis of the Eurocentric worldview. The purpose of this article is to initiate a process of radical reinterpretation of traditional meanings of classical philosophy due to their irrelevance in the solution of modern sociocultural problems, in particular, the problem of establishing tolerant relationships between different cultures within the globalizing world